Internal short circuit detection for lithium-ion battery pack with parallel-series hybrid connections. (10th May 2020) - Pan, Yue; Feng, Xuning; Zhang, Mingxuan; Han, Xuebing; Lu, Languang; Ouyang, Minggao
Abstract: Internal short circuit is one of the unsolved safety problems that may trigger the thermal runaway of lithium-ion batteries. This paper aims to detect the internal short circuit that occurs in battery pack with parallel-series hybrid connections based on the symmetrical loop circuit topology. The theory of the symmetrical loop circuit topology answers the question that: 1) How to locate an exact internal short circuit fault in a battery pack with hybrid electric connections. 2) What kind of signal is needed for detecting the fault; 3) The minimum requirement of using additional Ampere Meters for fault diagnosis. The Ampere Meters extract new signal that reflects the imbalanced current among the parallel-connected cells. The internal short circuit is judged according to the number theory and the circuit topology. Algorithm using recursive least square locks the fault cell online. Substitute internal short circuit experiments validate the proposed algorithm at pack level. The proposed approach detects the fault of internal short circuit efficiently and accurately, having great potential to be applied in the fault diagnosis of battery pack for large scale energy storage systems. Highlights: An internal short circuit (ISC) detection method for lithium-ion battery is proposed. The ISC detection algorithm is addressed from number theory and circuit topology. The algorithm can detect ISC based on signals extracted from Ampere Meters. The algorithm can detect ISC with a resistance of smaller than 10Ω within 15 s.